Data From the MySWOW Proof-of-Concept Study: Linking Individual Semantic Networks and Cognitive Performance. (29th March 2022) - Wulff, Dirk U.; Aeschbach, Samuel; De Deyne, Simon; Mata, Rui
We report data from a proof-of-concept study involving the concurrent assessment of large-scale individual semantic networks and cognitive performance. The data include 10, 800 free associations—collected using a dedicated web-based platform over the course of several weeks—and responses to several cognitive tasks, including verbal fluency, episodic memory, associative recall tasks, from four younger and four older native German speakers. The data are unique in scope and composition and shed light on individual and age-related differences in mental representations and their role in cognitive performance across the lifespan.